Sketching user experiences : getting the design right and the right design - Buxton, William (Interactive Technologies., 2007)
Bill Buxton and I share a common belief that design leadership together with technical leadership drives innovation. Sketching, prototyping, and design are essential parts of the process we use to create new products. Bill Buxton brings design leadership and creativity to Microsoft. Through his thought-provoking personal examples he is inspiring others to better understand the role of design in their own companies--Bill Gates, Chairman, Microsoft"Informed design is essential." While it might seem that Bill Buxton is exaggerating or kidding with this bold assertion, neither is the case. In